The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s00330-005-2758-1
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous laser-assisted recanalization of long chronic iliac artery occlusions: primary and mid-term results

Abstract: We report the primary and mid-term outcome of patients with long chronic iliac artery occlusions after percutaneous excimer-laser-assisted interventional recanalization. Between 2000 and 2001, 43 patients with 46 chronic occlusions of either the common iliac artery (n=27), the external iliac artery ( n=13) or both (n=3) underwent laser-assisted percutaneous transluminal angioplasty and implantation of stents. The average length of the occlusion was 57.1+/-26 mm. After laser-assisted angioplasty and implantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…A small study with 43 patients demonstrated feasibility of laser angioplasty in chronic iliac occlusions with a technical success rate of 95.3%. 26 However, the efficacy of laserassisted recanalization in iliac occlusions needs to be validated in larger studies.…”
Section: Discussionmentioning
confidence: 99%
“…A small study with 43 patients demonstrated feasibility of laser angioplasty in chronic iliac occlusions with a technical success rate of 95.3%. 26 However, the efficacy of laserassisted recanalization in iliac occlusions needs to be validated in larger studies.…”
Section: Discussionmentioning
confidence: 99%
“…1 Diffuse severe calcification, which may often be present in patients receiving long-term hemodialysis, 4 may be one of causes of procedural failure after successful guidewire passage, although it is rare. These limitations, which are common in percutaneous coronary intervention (PCI), have led to the development of new devices.…”
Section: Discussionmentioning
confidence: 99%
“…1 One of the causes of failure is the inability to cross the lesion with a balloon angioplasty catheter. The use of the Tornus microcatheter (Asahi Intecc, Aichi, Japan) to overcome this limitation has recently been approved by the United States Food and Drug Administration (Fig 1).…”
mentioning
confidence: 99%
“…No association could be made between the duration or the severity of the clinical signs and the clinical outcome. The success of this procedure is in the authors' opinion, dependent on the length of the occlusion in which the thrombus is adhered to the arterial wall, as described in human literature (Colapinto et al 1986;Balzer et al 2006). It seems that intraoperatively if the thrombus is only loosely adhered to the arterial wall the prognosis is more favourable than if the thrombus adheres tightly.…”
Section: Manufacturers' Addressesmentioning
confidence: 91%
“…With the repeated use of the Fogarty catheter, which tears the thrombus out of the artery, damaging of the arterial wall occurs. Improvement of the technique might be obtained by the use of an excimer laser for debulking the thrombus, and stent implantation (Balzer et al 2006), reducing the chance of restenosis. However, in human patients, a 3 mm laser canal is created and then the implant is inserted after balloon dilation (Balzer et al 2006).…”
Section: Manufacturers' Addressesmentioning
confidence: 99%